Research-to-practice conference as a component of improving knowledge and mastering professional competencies by medical students and young scientists - V. N. Larina; E. V. Kudina; K. R. Mikava; A. A. Gavrilova (Кардиоваскулярная терапия и профилактика, 2024)
Aim. To evaluate the importance of certain aspects of research-to-practice conferences, organized by the Department of General Practice of Pirogov Russian National Research Medical University, as well as its contribution to preparing students for future professional activities within the outpatient healthcare and the impact of these events on the interest of participants and speakers for research work.Material and methods. An anonymous online survey included 37 participants in the discussed conferences regarding the respondents’ motivation to attend conferences, assessment of declared subject coverage, the practical applicability of the knowledge gained and other aspects.Results. The most important motivating factors for conference participation were interest in outpatient healthcare (52,4% for the conference "Internal diseases at the prehospital stage" and 87,5% for the conference "A multimorbid patient — continuity between hospital and clinic"), analysis of interesting cases (66,7% and 75%, respectively) and multidisciplinary focus of activities (47,6% and 68,8%). An important aspect was the coverage of current problems of practical healthcare. The most important results were considered by the majority of participants to be expanding their medical horizons (85,7% and 87,5%) and gaining new knowledge on the declared subject (90,5% and 75%). Almost half of the respondents (52,4% and 56,3%) improved their interest in scientific activities as a result of visiting the conferences.Conclusion. Conducting research-to-practice conferences for students, residents and postgraduates serves as a platform for increasing the knowledge and mastering professional competencies. The results of a survey of conference participants and speakers indicate the relevance of involving students in conferences and the numerous benefits they receive, which are discussed in detail in this article.